Pengembangan Media Pembelajaran Interaktif pada Mata Pelajaran Dasar-Dasar Teknik Elektronika di SMKN 4 Pariaman - Fauzi, Alrian; Efrizon, Efrizon (TSAQOFAH, 2025)
This study is driven by the need for effective and engaging instructional media to support students’ understanding of the subject Dasar-Dasar Teknik Elektronika (Fundamentals of Electronics Engineering) at SMK Negeri 4 Pariaman. The purpose of this research is to develop an interactive learning medium based on Canva and to assess its validity and practicality. The study employed a Research and Development (R&D) method involving all 20 tenth-grade students of the Industrial Electronics Engineering program as the sample. Data were collected through validation questionnaires completed by two media experts and two subject matter experts, as well as a practicality questionnaire administered to students as end users. Data analysis involved calculating the feasibility percentage from the validation scores and the average student response score using a Likert scale. The results showed that the developed media is valid, with validation scores of 95% from media experts and 94.37% from subject matter experts, and practical, with a practicality score of 90.18%. These findings indicate that the Canva-based interactive learning medium is suitable for use and effectively supports students in understanding basic electronics engineering concepts. Therefore, this medium can serve as an appealing, accessible, and relevant instructional aid aligned with the needs of vocational education in the digital era.